Garag sheep phenotype and husbandry in Um Hani area in the White Nile State, Sudan - E. Elimam, Mohmed; A. A. Bashir, Abdellatif (Gezira Journal of Agricultural Science; Vol 11 No 1 (2013), 2013)
Garag sheep phenotype and husbandry were studied in a survey of 295 animals at <1 - >4 years old in Um Hani area in the White Nile State, Sudan. Body weight (BW) and measurements generally increased with age from <1 to 4 years old. The tail was below the hock joint in most animals. The hair was short and rough and the coat colour varied and was mainly white (73.89% in females and 64.44% in males),  black and white (9.49% in females and 17.78% in males) and white and red (5.08% in females and 6.67% in males). The face profile was convex and the animals were polled. There were strong correlations between BW and measurements and different linear regression equations were used to predict BW from heart girth (HG), height at withers (HW) and body length (BL) with no significant differences between measured and predicted BW. Flock size was 80.78 and females formed most of the flocks (88.37%). Lambs were weaned at 4.24 months old. Age at puberty was 6.82 months in males and 7.2 months in females. Age at first service was 8.12 months in males and 7.96 months in females. Gestation period was 154.2 days. Lambing interval was 356.4 days and lambing was from August to September. Lactation period was 124.8 days and average milk yield was 0.37 kg/day. Longevity was higher in females (6.48 years) than males (3.8 years).